Wookiee Statements, Semanticism, and Reasonable Assertion - GARCÍA RAMÍREZ, Eduardo (Revista de Filosofía, 2011)
It is assumed that the content of an assertion is determined either by the semantically defined content or by the interaction of the latter with the context. Here I present a counterexample by means of the Wookiee problem. After considering several options I offer what appears to be its most satisfactory solution. This requires that we give up the assumption in favor of a view according to which it may be that semantic information does not at all determine the content of an assertion, not even partly so.